Serum anticholinergic activity and cerebral cholinergic dysfunction: an EEG study in frail elderly with and without delirium - Thomas, Christine; Hestermann, Ute Marion; Kopitz, Jürgen; Plaschke, Konstanze; Oster, Peter; Driessen, Martin; Mundt, Christoph; Weisbrod, Matthias (BMC neuroscience, 2008)
Delirium increases morbidity, mortality and healthcare costs especially in the elderly. Serum anticholinergic activity (SAA) is a suggested biomarker for anticholinergic burden and delirium risk, but the association with cerebral cholinergic function remains unclear. To clarify this relationship, we prospectively assessed the correlation of SAA with quantitative electroencephalography (qEEG) power, delirium occurrence, functional and cognitive measures in a cross-sectional sample of acutely hospitalized elderly (> 80 y) with high dementia and delirium prevalence.